The Effect of Therapeutic Communication on Social Isolation Clients in Sidikalang Regional General Hospital in 2019 - Hutagalung, Perak M.A. (Budapest International Research and Critics University, 2021)
This study aims to identify the effect of therapeutic communication on social isolation clients at the Sidikalang Regional General Hospital in 2019. The research methodology used in this study is a case study that uses a quasi-experimental research design with a one group pre post test design approach. This study only tested one group of subjects where the group was observed before the intervention was then observed again after the intervention. The results of the study were based on the characteristics of the research subjects, 2 men (100%), 1 person (50%) 21 years old, 1 23 year old subject (50%), 2 unmarried subjects (100%), Subjects with a junior high school education of 1 person (50%), 1 person with a high school education (50%), and a subject whose occupation is self-employed 2 people (100%). The level of social isolation before therapeutic communication was carried out in the first subject there was a moderate level of social isolation (score 6), in the second subject there was a moderate level of social isolation (score 6) and on average from both subjects there was a moderate level of social isolation (score 6). The level of social isolation after therapeutic communication was carried out in the first subject there was a mild level of social isolation (score 4), in the second subject there was a mild level of social isolation (score 2) and on average from both subjects there was a mild level of social isolation (score 3).